Implementasi Six Sigma untuk Meminimalisasi Reject Material Preform pada PT Z - Pramesti, Regista Ardea; Sukanta, Sukanta; Winarno, Winarno (Fakultas Teknik Universitas Tulang Bawang, 2026)
The high rate of product defects (rejects) in the production process directly impacts the efficiency of PT Z, a company engaged in the production of Bottled Drinking Water (AMDK). PT Z encountered a reject rate of preform material reaching 4.07% in July 2023, equivalent to 352,875 defective units out of a total of 8,674,644 units produced. This study aims to reduce the reject rate of preform material by implementing the Six Sigma method using the DMAIC approach (Define, Measure, Analyze, Improve, and Control). The analysis was conducted using Pareto and fishbone diagrams to identify the root causes of defects, which include human, machine, and material factors. The results showed a decrease in DPMO from 194,927.79 to 46,803.66, an increase in Sigma Level from 2.52 to 3.23, and a reduction in the reject rate from 4.07% to 1.17%. These findings confirm that the Six Sigma approach is effective in identifying defect causes and significantly improving production process quality in the bottled water industry. Keywords: DPMO (Defects Per Million Opportunities), Quality Improvement, Reject Preform Material, Sigma Level, Six Sigma